A nickel based superalloy reinforced by both Ni3Al and Ni3V ordered-fcc precipitates. (15th March 2019) - J Knowles, Alexander; Reynolds, Lucy; A Vorontsov, Vassili; Dye, David
Abstract: A nickel based superalloy has been designed where the fcc γ Ni matrix is reinforced by two different ordered-fcc intermetallic compounds, γ ′ L12 Ni3 Al and γ ′ ′ D022 Ni3 V. Primary ageing at 900–1000 °C precipitated spherical L12 Ni3 Al, whose volume fraction and size were controlled by altering the ageing temperature and time. Secondary ageing at 700 °C for 1–1000 h precipitated D022 Ni3 V laths. The duplex precipitation increased hardness by up to 85 HV, with ∼ 500 MPa compressive proof strength maintained at 800 °C. Electron microscopy studied the Ni3 Al precipitation and confirmed the form of the secondary Ni3 V precipitates and their long term stability. Graphical Abstract: